RELEVANSI DIKLAT TEKNIS SUBSTANTIF GURU MATEMATIKA TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Euis Setiawati (Balai Diklat Keagamaan Bandung, 2021)
This article aims to describe the relevance of implementing Substantive Education and Training for Mathematics Teachers in terms of improving mathematical creative thinking ability on Islamic elementary, Junior, and Senior High Schools teachers. The population was mathematics teachers who joined training held by Religious Training Center in four regions: Bandung, Semarang, Jakarta, and Surabaya. The research sample consisted of 85 participants. The independent variable of the research is the relevance of Substantive Education and Training for Mathematics Teachers, and mathematical creative thinking ability as the dependent. Mathematical creative thinking ability is viewed from the teacher levels. To measure the relevance, the method uses multiple linear regression tests after taken classical assumption test. The result shows the value F_countF_table= 39,312 3,10, so H0 is rejected, meaning it has significant relevance between the implementation of Substantive Education and Training for Mathematics Teachers to the improvement of mathematical creative thinking ability on all Islamic teachers in the levels of Elementary, Junior, and Senior High Schools who involved.Keywords: relevance; education and training; mathematical creative thinking ability